2002
DOI: 10.1063/1.1408302
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring the water dimer potential energy surface with explicitly correlated computations and focal point analyses

Abstract: Ten stationary points on the water dimer potential energy surface have been characterized with the coupled-cluster technique which includes all single and double excitations as well as a perturbative approximation of triple excitations [CCSD(T)]. Using a triple-ζ basis set with two sets of polarization functions augmented with higher angular momentum and diffuse functions [TZ2P(f,d)+dif], the fully optimized geometries and harmonic vibrational frequencies of these ten stationary points were determined at the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
257
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 271 publications
(294 citation statements)
references
References 68 publications
33
257
4
Order By: Relevance
“…29) or 12 cm −1 (Ref. 30). One should mention here that simple harmonic calculations predict IR frequency shifts reasonably well, in contrast to predictions of the intermonomer transition frequencies.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…29) or 12 cm −1 (Ref. 30). One should mention here that simple harmonic calculations predict IR frequency shifts reasonably well, in contrast to predictions of the intermonomer transition frequencies.…”
Section: Introductionmentioning
confidence: 84%
“…The symbol q X stands for the set of three internal coordinates of monomer X(= A, B), and q ref refers to a reference geometry, for which we take the vibrationally averaged structure. The quality of this flexible-monomer potential surface can be checked, among other things, by comparing the characteristics of the global minimum with the benchmark calculations of Tschumper et al 30 Table I shows (the dimer interatomic distances and angles are defined in Fig. 1) that intermonomer parameters are reproduced by SAPT-5s fIR with a few-percent errors: the binding energy D e with 5.2%, the 32 that deficiencies of SAPT-5s compared to CCpol-5s result mainly from the smaller basis set used to develop the former potential.…”
Section: A Flexible Ccpol-8s Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, for any tolerance δ we can define an effective radius R δ of the cluster with ∫r>R δ ρ ∼ tot (r)dr < δ. (27) Let T>2R δ , and for any site s∈S n and any α, t, u, and v, define the periodic extension of …”
Section: F Increasing Computational Efficiency Using Reciprocal Spacmentioning
confidence: 99%
“…This contribution is generally misrepresented, diminishing the anisotropy of the interactions. 1 van Duijneveldt-van de Rijdt et al 9 recently tested several available molecular mechanics potentials on the difficult ten stationary points of the water dimer potential energy surface as described by Tschumper et al 10 They concluded that in order for a force field to be both accurate and transferable, i.e., useful for a range of similar systems, it must separately reproduce each of the four physical components of the total intermolecular interaction energy, namely, Coulomb, exchange repulsion, induction, and dispersion. In this context, the sum of interacting fragment ab initio (SIBFA) force field, 11 initially tested in the paper of van Duijneveldt-van de Rijdt's et al, was recently refined in order to more closely reproduce each of the individual components of the Hartree-Fock intermolecular interaction energy.…”
Section: Introductionmentioning
confidence: 99%